One can be some but some cannot be one: ERP correlates of numerosity incongruence are different for singular and plural. (July 2019) - Arcara, Giorgio; Franzon, Francesca; Gastaldon, Simone; Brotto, Silvia; Semenza, Carlo; Peressotti, Francesca; Zanini, Chiara
Abstract: Humans can communicate information on numerosity by means of number words (e.g., one hundred, a couple ), but also through Number morphology (e.g., through the singular vs the plural forms of a noun). Agreement violations involving Number morphology (e.g., * one apples ) are well known to elicit specific ERP components such as the Left Anterior Negativity (LAN); yet, the relationship between a morphological Number value (e.g., singular vs plural) and its referential numerosity has rarely been considered in the literature. Moreover, even if agreement violations have been proven to be very useful, they do not typically characterise everyday language usage, thus narrowing the scope of the results. In this study we investigated Number morphology from a different perspective, by focusing on the ERP correlates of congruence and incongruence between a depicted numerosity and noun phrases. To this aim we designed a picture–phrase matching paradigm in Italian. In each trial, a picture depicting one or four objects was followed by a grammatically well-formed phrase made up of a quantifier and a content noun inflected either in the singular or in the plural. When analysing ERP time-locked to the content noun, plural phrases after pictures presenting one object elicited a larger negativity, similar to a LAN effect. No significant congruence effect was found in the case of the phrases whose morphological Number value conveyed a numerosity of one. Our results suggest that: 1) incongruence elicits a LAN-like negativity independently from the grammaticality of the utterances and irrespectively of the P600 component; 2) the reference to a numerosity can be partially encoded in an incremental way when processing Number morphology; and, most importantly, 3) the processing of the morphological Number value of plural is different from that of singular as the former shows a narrower interpretability than the latter.